Full Ground Plane Dual-Band Microstrip Antenna for ISM and HiperLAN/2 Applications - Yew, B.S; Mohd Rizon, Mohamed Juhari; Saiful Bahri, Mohamed (2014)
A full ground plane dual band microstrip antenna (FGP-DBMA) over ISM and HiperLAN/2 applications is presented. The structural design of the FGP-DBMA is based on suspended plate antenna. The FGP-DBMA antenna features a 56 × 55 mm2 rectangular radiating element suspended over 90 × 90 mm2 ground plane. ShieldIt Super conductive textile features are used as the radiating element and ground plane while felt textile features are used as the dielectric substrate. The rectangular radiator patch is designed using slits for dual-band resonance over ISM band (2.4 GHz to 2.48 GHz) and HiperLAN/2 band (5.725 GHz to 5.875 GHz). The FGP-DBMA radiates unidirectional with a fully grounded plane to avoid coupling onto user’s body. The FGP-DBMA shows efficiency over the range of 69.6 % to 75.6 % and gain over the range of 6.052 dB to 6.323 dB in the free space scenario. The evaluation of FGP-DBMA with bending effects shows no significant changes to the performance of the FGP-DBMA. This indicates that the curvature effect on the proposed FGP-DBMA for on-body performance, i.e. on human arm, does not affect the performance of the antenna.